The influence of family ownership, family involvement, and founder generation on dividend policy: evidence from non-cyclical consumer family firms in Indonesia (2019–2023) - Firdaus, Matteo; Rosdini, Dini; Kanti, Runita Arum (Universitas Padjadjaran, 2026)
Family firms play a pivotal role in shaping Indonesia’s economic landscape, with their unique governance structures influencing key financial decisions such as dividend distribution. This study provides an in-depth examination of how family ownership, family involvement, and the generational status of the founder shape dividend policy among 24 non-cyclical consumer family firms listed on the Indonesia Stock Exchange (IDX) over the period 2019–2023. Firm size and profitability are incorporated as control variables to ensure the robustness of the analysis. Employing panel data regression techniques, the study uncovers several notable findings. First, family ownership exerts a positive and statistically significant influence on dividend policy, suggesting that higher equity control by families encourages more generous dividend payouts to meet family income needs and signal financial health. Conversely, active family involvement in management and the continuation of leadership under the founder generation are both found to have negative and significant impacts, indicating a preference for profit retention to support internal growth and maintain control rather than distributing earnings. Among the control variables, profitability emerges as a strong positive determinant of dividend payouts, reflecting the firm’s capacity to return earnings to shareholders. In contrast, firm size does not demonstrate a significant effect, implying that scale alone does not dictate dividend behaviour in this context. These findings align with agency theory and signaling theory, illustrating that dividend policy in Indonesian family firms is a complex interplay of family control motives, generational leadership strategies, and operational performance. The study highlights that while family ownership encourages dividend distribution, direct family involvement and founder-led governance tend to prioritise long-term stability and strategic reinvestment over short-term payouts.